FORMATION OF RESEARCH COMPETENCE OF STUDENTS-ECONOMISTS BY MEANS OF FOREIGN LANGUAGE - Gulnara Faritovna Kalganova; Marina Gennadievna Kudryavtseva (Sovremennye Issledovaniâ Socialʹnyh Problem, 2017)
The problem of forming research competences as part of professional competencies is considered when implementing educational standards of the third generation. Knowledge of a foreign language and its use as a tool for searching, selecting and extracting information of a scientific and / or specialized nature acquire special relevance in the context of globalization not only of information resources but also of the modern labor market. The involvement of students in research activities in a foreign language contributes to the formation of additional research competencies.